Pengaruh Fuzzy Logic Controller Pada Pengoperasian Filter Aktif Shunt Terhadap Penurunan ITHD dan Rugi-Rugi Daya Pada Sistem Kelistrikan RSUD Klungkung - Jerry Akira Dinata, I Putu; Rinas, I Wayan; Arta Wijaya, I Wayan (Jurnal SPEKTRUM, 2019)
RSUD Klungkung is supplied by a transformer with a capacity of 200 kVA. The use of non-linear loads in Klungkung Hospital can cause harmonic currents (ITHD). The greater the harmonic current produced, the quality of the electrical power will get worse, causing losses to the transformer. The installation of active shunt filters and the use of fuzzy logic controllers as controllers on filters can reduce the harmonics that occur in the electrical system. The results of ITHD measurements on existing conditions for R phase are 11.23%, S phase is 14.72%, and T phase is 11.20%. The ITHD value decreased when the system was paired with a shunt active filter for R phase of 5.24%, S phase was 7.18%, and T phase was 5.34%. The ITHD value has decreased again when the use of fuzzy logic controller for R phase is 0.15%, S phase is 0.17%, and T phase is 0.11%. Decreasing ITHD values affect the losses generated on the system. In the existing conditions losses are 10.525%, losses in the operation of the shunt active filter are 1.352%, and the use of fuzzy logic controller produces the smallest losses of 0.00035%.